1997
DOI: 10.1103/revmodphys.69.865
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics and breakup of free-surface flows

Abstract: Surface-tension-driven flows and, in particular, their tendency to decay spontaneously into drops have long fascinated naturalists, the earliest systematic experiments dating back to the beginning of the 19th century. Linear stability theory governs the onset of breakup and was developed by Rayleigh, Plateau, and Maxwell. However, only recently has attention turned to the nonlinear behavior in the vicinity of the singular point where a drop separates. The increased attention is due to a number of recent and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
1,402
2
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,638 publications
(1,468 citation statements)
references
References 202 publications
53
1,402
2
11
Order By: Relevance
“…The values of X given by similarity solutions under different conditions have been summarized by McKinley and Tripathy 19 . When inertia is important and Oh ≪ 1, X = 0.5912 is the value most likely to be observed in an experiment 19,25,26 and hence t * 1 2 → 0.7135 as Oh → 0. When viscosity is dominant on the other hand, X = 0.7127 19,27 and t * 1 2 → 7.0522 Oh as Oh → ∞.…”
Section: Extensional Viscosit Suspensions Of Motimentioning
confidence: 82%
“…The values of X given by similarity solutions under different conditions have been summarized by McKinley and Tripathy 19 . When inertia is important and Oh ≪ 1, X = 0.5912 is the value most likely to be observed in an experiment 19,25,26 and hence t * 1 2 → 0.7135 as Oh → 0. When viscosity is dominant on the other hand, X = 0.7127 19,27 and t * 1 2 → 7.0522 Oh as Oh → ∞.…”
Section: Extensional Viscosit Suspensions Of Motimentioning
confidence: 82%
“…Downstream of breakup point, the jet solution no longer has physical meaning, since the jet in that region will have broken up into droplets, which cannot be described by this approach, as is also the case in other works. [6][7][8]11 The solutions obtained can be put on the physical plane x − z in the following way:…”
Section: Methodsmentioning
confidence: 99%
“…These equations (13) and (14) were also obtained before for straight axisymmetric jets by other authors. 6,7,11 However, the rotation of the container Ω enters the formulation via the initial conditions for the above system of equations, and so this system is fundamentally different to those for straight jets. We shall see in the following sections how the solutions to these equations depend critically upon the rotation of the container, and how therefore the solution to this system of equations is different to the solution of the straight jet equations.…”
Section: T)mentioning
confidence: 99%
“…The topic of finite-time rupture has been treated by many authors, such as Erneux & Davis (1993), Ida & Miksis (1996) and Vaynblat, Lister & Witelski (2001a) for viscous sheets and Papageorgiou (1995), Eggers (1997) and Renardy (2001) for viscous threads. Vaynblat, Lister & Witelski (2001b) have shown that lubrication models for van der Waals driven rupture of a sheet and capillary driven rupture of a thread both give rise to families of first-kind similarity solutions.…”
Section: Introductionmentioning
confidence: 99%